Time of Day Matters: An Exploratory Assessment of Chronotype in a Forensic Psychiatric Hospital - Belfry, Kimberly D.; Deibel, Scott H.; Kolla, Nathan J. (Frontiers in Psychiatry, 2020)
A growing body of evidence links the late chronotype to mental illness, aggression, and aversive personality traits. However, much of what we know about these associations is based on healthy cohorts, and it is unclear how individuals with high levels of aggression, including forensic psychiatric populations, but not offenders, are affected. The present study aimed to measure chronotype in a forensic psychiatric inpatient population, evaluate the impact of diagnosis, and identify any interactive relationships between chronotype, diagnosis, aggression, and dark triad traits. Subjects completed the reduced morningness-eveningness questionnaire (rMEQ), Munich chronotype questionnaire (MCTQ), Pittsburg sleep quality index (PSQI), short form Buss Perry aggression questionnaire (BPAQ-SF), and short dark triad questionnaire (SD3). We sampled 55 forensic psychiatric patients (52 males) between the ages of 23 and 73 years (mean ± SD: 39.6 ±14.3 years). Among the patients sampled, 25% were evening types and 36% were morning types. Eveningness was greater in patients with a personality disorder; however, no chronotype differences were found for psychosis patients. Patients without psychosis had a positive association between anger and eveningness, as well as between hostility and eveningness. For subjects with a substance use disorder, morningness was positively associated with narcissism. Conversely, an association between eveningness and greater narcissism was identified in patients who did not have a substance use disorder. These findings suggest that, compared to the general population, evening types are more prevalent in forensic psychiatric populations, with the strongest preference among patients diagnosed with a personality disorder. No differences in chronotype were identified for psychosis patients, which may be related to antipsychotic medication dosing. Given the sex distribution of the sample, these findings may be more relevant to male populations.